Covid-19 Incidence and Mortality by Age Strata and Comorbidities in Mexico City: A Focus in the Pediatric Population - González-García, Nadia; Castilla-Peón, María F.; Solórzano Santos, Fortino; Jiménez-Juárez, Rodolfo Norberto; Martínez Bustamante, Maria Elena; Minero Hibert, Miguel Angel; Garduño-Espinosa, Juan (Frontiers in Public Health, 2021)
Background. SARS-COV2 appears less frequently and less severely in the pediatric population than in the older age groups. There is a need to precisely estimate the risks specific for each age group to design health and education policies suitable for each population Objective. This study aimed to describe the risk of death in SARS-COV2 infected subjects by age group and according to the presence of comorbidities. Methods. We analyzed data of confirmed SARS-COV2 infection cases where symptoms began between February 22th, 2020, and March 31, 2021, as published by the General Epidemiology Direction (DGE) of the Mexican Ministry of Health. We calculated COVID-19 incidence and mortality by age group using population data from the Statistics and Population National Institute (INEGI) and estimated the association between risk of death and the presence of comorbidities. Results. Mortality in SARS-COV2 infected people varied considerably, between 7 to 155 deaths per million per year in the under-20 age groups compared to 441 to 15929 in the older age groups. Mortality in pediatric populations is strongly associated with comorbidities (OR: 4.6- 47.9) compared to the milder association for older age groups (OR: 3.16-1.23). Conclusions. The risk of death from SARS-COV2 infection in children is low and is strongly associated with comorbidities.